Collapse risk assessment of a Chilean dual wall-frame reinforced concrete office building. (15th March 2019) - Araya-Letelier, G.; Parra, P.F.; Lopez-Garcia, D.; Garcia-Valdes, A.; Candia, G.; Lagos, R.
Highlights: A Chilean code-conforming reinforced concrete office building is designed. Incremental dynamic analyses of the building are performed using 45 ground motions. Two collapse fragility curves and two seismic hazard curves are proposed. Estimated mean annual frequencies of collapse were in the order of 10 −5 –10 −4. Estimated probabilities of collapse in 50 years were in the order of 0.1–0.7% Abstract: Several code-conforming reinforced concrete buildings were severely damaged during the 2010 moment magnitude (Mw ) 8.8 Chile earthquake, raising concerns about their real collapse margin. Although critical updates were introduced into the Chilean design codes after 2010, guidelines for collapse risk assessment of Chilean buildings remain insufficient. This study evaluates the collapse potential of a typical dual system (shear walls and moment frames) office building in Santiago. Collapse fragility functions were obtained through incremental dynamic analyses using a state-of-the-art finite element model of the building. Site-specific seismic hazard curves were developed, which explicitly incorporated epistemic uncertainty, and combined with the collapse fragility functions to estimate the mean annual frequency of collapse (λc ) values and probabilities of collapse in 50-years (Pc (50)). Computed values of λc and Pc (50) were on the order of 10 −5 –10 −4, and 0.1–0.7%, respectively, consistent with similar studies developed for buildings in the US. The results also showed that the deaggregation of λc was controlled by small to medium earthquake intensities and that different models of the collapse fragility functions and hazard curves had a non-negligible effect on λc and Pc (50), and thus, propagation of uncertainty in risk assessment problems must be adequately taken into account.